Decree No. 1/A of 1989 promulgating the Executive Statues of the law on Civil Aviation - Egypt (2025)
Ministerial Decree No. 1/A of the year 1989 promulgating the executive statutes of the civil Aviation Law – Ministry of civil Aviation Decree No. 1/A of the year 1989 promulgating the executive statutes of the civil Aviation Law